Portal hemodynamic changes after hepatocyte transplantation in acute hepatic failure - Yu, Chun-Hsien; Chen, Hui-Ling; Chen, Wei-Tsung; Ni, Yen-Hsuan; Lin, Yah-Luen; Chang, Mei-Hwei (Journal of biomedical science, 2004)
Hepatocyte transplantation has been proposed as an alternative for rescuing patients with acute hepatic failure. However, portal hemodynamic changes and issues of safety after hepatocyte transplantation in acute hepatic failure have not been systemically evaluated because of the lack of a suitable experimentation system. In this study, we created a novel spring-guidewire introducer needle to simplify the technique for long-term portal cannulation in F-344 rats. The portal cannula was capable of being used for blood sampling, infusion of hepatocytes, and measurement of portal hemodynamic changes. One week after portal cannulation, rats were injected with D-galactosamine (1.35 g/kg, i.p.) to induce hepatic failure. Hepatocytes (2 x 10(7)) were infused intraportally 24-26 h after induction of liver injury. Portal pressures were recorded for up to 60 min after hepatocyte transplantation. Intraportal infusion of 2 x 10(7) hepatocytes caused an instantaneous onset of portal hypertension. The magnitude of the rise in portal pressure was similar in both normal rats and rats with acute hepatic failure (33.0 +/- 7.1 vs. 37.7 +/- 0.5 mm Hg; p = 0.23). However, the resolution rate of portal hypertension was remarkably delayed in rats with acute hepatic failure, and the portal pressure was significantly higher than that in normal rats 60 min after hepatocyte transplantation (25.0 +/- 2.8 vs. 14.5 +/- 2.4 mm Hg; p = 0.007). In conclusion, we have established a simple new technique for long-term portal cannulation of rats. Our studies provide critical insights into the delayed resolution of portal hemodynamics after hepatocyte transplantation in subjects with acute hepatic failure.